Special judo fitness test level and anthropometric profile of elite Spanish judo athletes - Casals, C.; Huertas, J. R.; Franchini, E.; Sterkowicz-Przybycien, K.; Sterkowicz, S.; Gutiérrez-Garcia, C.; Escobar-Molina, R. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to determine the anthropometric variables that best predict Special Judo Fitness Test (SJFT) performance. In addition, anthropometric profiles of elite Spanish judo athletes were compared by sex and age category (seniors and juniors). In this cross-sectional study, a total of 51 (29 females) athletes from the Spanish National Judo Team were evaluated during a competitive period. All athletes performed the SJFT and underwent an anthropometric assessment through skinfold thickness measurements. Mann-Whitney comparisons by sex and age category showed that males had significantly higher muscle mass and lower fat mass than females (p < 0.001), whereas juniors and seniors exhibited few differences in body composition. Linear regression analyses (stepwise method) were performed to explore the relationships between anthropometric characteristics and SJFT variables. Model 1 included sex, age category, and body mass as predictors. Body mass and sex significantly predicted the SJFT index (R2 = 0.27, p < 0.001); thus, both criteria should be considered before interpreting the test. The predictors of model 2 were quick-assessment variables, including skinfolds, breadths, girths, and height. This regression model showed that the biceps skinfold significantly predicted the SJFT index in elite athletes (R2 = 0.31, p < 0.001). Model 3 included body compositions and somatotypes as predictors. Higher muscle and bone masses and lower ectomorphy were associated with better SJFT performance (R2 = 0.44, p < 0.001). Hence, training programs should attempt to increase the muscle mass percentage and reduce the upper arm fat, whereas the bone percentage could be considered in the selection of talented athletes in conjunction with other factors.